2023
DOI: 10.1039/d3cc00787a
|View full text |Cite
|
Sign up to set email alerts
|

Lewis/Brønsted acid-mediated cyclization/amidation of 1,6-enynes with nitriles: access to 3-enamide substituted dihydrobenzofurans

Abstract: A novel Lewis- and Brønsted-acid mediated cyclization/amidation reaction of 1,6-enynes with nitriles to synthesize 3-enamide-substituted dihydrobenzofurans has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…The mechanism study found that the reaction might be initiated with a radical process and a carbamate complex of Cu(II) might be the active intermediate in the reaction. Similarly, we also elucidated a metal-free method for the transformation of nitriles and 1,6-enynes into enamide-substituted dihydrobenzofurans . The synergistic effect of a Lewis acid and Brønsted acid is very crucial for the success of the reaction.…”
Section: Synthesis Of Oxygen-containing Heterocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism study found that the reaction might be initiated with a radical process and a carbamate complex of Cu(II) might be the active intermediate in the reaction. Similarly, we also elucidated a metal-free method for the transformation of nitriles and 1,6-enynes into enamide-substituted dihydrobenzofurans . The synergistic effect of a Lewis acid and Brønsted acid is very crucial for the success of the reaction.…”
Section: Synthesis Of Oxygen-containing Heterocyclesmentioning
confidence: 99%
“…Similarly, we also elucidated a metal-free method for the transformation of nitriles and 1,6enynes into enamide-substituted dihydrobenzofurans. 37 The synergistic effect of a Lewis acid and Brønsted acid is very crucial for the success of the reaction.…”
Section: Benzofuranmentioning
confidence: 99%
“…3). There have been many processes reported for the synthesis of dihydrobenzofurans in the past decades that involve the use of different catalytic systems, i.e., acid or base catalyzed synthesis, [24][25][26] organocatalysis, 27 salt catalyzed synthesis 28 as well as electrochemical and photochemical synthesis. 29,30 Transition metal (TM)-catalyzed reactions involving the synthesis of dihydrobenzofuran skeletons are one of the most reliable and benecial methods.…”
Section: Introductionmentioning
confidence: 99%